2020
DOI: 10.1103/physreva.101.052504
|View full text |Cite
|
Sign up to set email alerts
|

Accurate deuterium spectroscopy and comparison with ab initio calculations

Abstract: We present accurate measurements of the quadrupole S(3) and S(4) transitions of the D2 2 − 0 band. Self-perturbed spectra were collected in a wide pressure range with a cavity ring-down spectrometer linked to an optical frequency comb. The results of ab initio quantum scattering calculations were incorporated into the line-shape analysis which was performed using the Hartmann-Tran profile. This approach allowed us to mitigate the collisional systematics and to reach a 900 kHz accuracy of the transition frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, the best measurements for the D 2 molecule, performed for the S(2) line from the first overtone, reached the accuracies of 500 kHz [16], 400 kHz [20] and even 161 kHz [23]. The first overtone in D 2 was also recently studied by Wójtewicz et al [24], who reported 870 and 999 kHz combined uncertainties for the positions of the S(3) and S(4) lines, respectively. Mondelain et al [25], estimated the uncertainty of the frequencies of the S(0) and Q(1)-Q(4) D 2 transitions between 0.3 and 1.83 MHz.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, the best measurements for the D 2 molecule, performed for the S(2) line from the first overtone, reached the accuracies of 500 kHz [16], 400 kHz [20] and even 161 kHz [23]. The first overtone in D 2 was also recently studied by Wójtewicz et al [24], who reported 870 and 999 kHz combined uncertainties for the positions of the S(3) and S(4) lines, respectively. Mondelain et al [25], estimated the uncertainty of the frequencies of the S(0) and Q(1)-Q(4) D 2 transitions between 0.3 and 1.83 MHz.…”
Section: Introductionmentioning
confidence: 83%
“…Theoretical studies of the rovibrational structure of the ground electronic state in molecular hydrogen achieve remarkable accuracy in the determined dissociation energy [1][2][3][4][5] and rovibrational energy levels [6][7][8][9][10][11][12]. The progress in the theoretical investigations is enhanced by recent experiments, which aim at the sub-MHz accuracy of both the dissociation energy [13,14] and the rovibrational transition frequencies in the ground electronic state [15][16][17][18][19][20][21][22][23][24][25][26][27]. Comparison between theoretical calculations and accurate measurements can be used as a test for the quantum electrodynamics for molecules [12], determination of the proton-charge radius [1,8,13,14] or even searches for physics beyond Standard Model [28], i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The FARS-CRDS is mostly used in conjunction with OFCs to take full advantage of both the methods for precision spectroscopy. For instance, high-resolution spectra of simple molecules such as D 2 which can help to correctly predict physical models have been probed by these techniques. Recently, an optical cavity with a staggering finesse of 6.37 × 10 5 was employed with FARS to probe the weak quadrupole line S(2) in the 2–0 band of D 2 around ∼1.6 μm with an average noise of 8 × 10 –12 cm –1 .…”
Section: Optical Cavity-based Advanced Techniquesmentioning
confidence: 99%
“…Recently, an optical cavity with a staggering finesse of 6.37 × 10 5 was employed with FARS to probe the weak quadrupole line S(2) in the 2–0 band of D 2 around ∼1.6 μm with an average noise of 8 × 10 –12 cm –1 . In a similar study, the S(3) and S(4) lines of D 2 , near the ∼1.56 μm region, in the same band were analyzed at high pressures (100–900 Torr). Careful line shape analysis was carried out through quantum scattering calculations to improve accuracy and test QED corrections.…”
Section: Optical Cavity-based Advanced Techniquesmentioning
confidence: 99%
“…Exact experimental vibrational levels for H2 and deuterium-bearing hydrogen molecules, i.e., hydrogen deuteride (HD) and dideuterium (D2) have been widely reported in the literature [3][4][5]. On the other hand, physical properties of the tritium-bearing hydrogen molecules, i.e., tritiated hydrogen (HT), deuterium-tritium (DT), and ditritium (T2), have been less frequently measured.…”
Section: ■ Introductionmentioning
confidence: 99%